How Ireland Voted 2024
L, 372 p. 95 illus., 92 illus. in color.
Keywords: ‘The indispensable guide to the election: invaluable statistics, revealing insights, astute analysis. A must-read for those interested in Irish politics.’ — David McCullagh, author, journalist and news presenter, RTÉ ‘The How Ireland Voted series is the go-to guide for each election, used to analyse the last election and prepare for the next. How Ireland Voted 2024 continues in that tradition with fascinating data, analysis and coverage of the whole election. Indispensable.’ — Mary Regan, Political Editor, Irish Independent ‘The book offers fascinating insights into party and voter dynamics during the 2024 Irish elections, all within the unique Irish party and electoral system. It’s exciting to see so many political scientists building on the growing wealth of high-quality research data to explore electoral and campaign behaviour in such depth and detail.’ — Professor Georg Lutz, University of Lausanne In 2024, all across the democratic world governments were being thrown out of office as far-right and other radical parties made breakthroughs. In Ireland, the conditions seemed favourable for change. An ongoing housing crisis, which had heightened Sinn Féin’s electoral expectations, and a turbulent year preceding the election, which had seen anti-immigration riots in Dublin city centre, suggested that Ireland might follow the international trends. Yet support for the incumbent Fianna Fáil and Fine Gael parties held up, and the government was returned to office, albeit with new junior partners. How did this happen? This tenth volume in the How Ireland Voted series provides the definitive analysis of the election. It covers the campaign, the results and voting behaviour, government formation, and has a particular focus on the reasons why there was no far-right breakthrough. With an overview of Ireland’s newly emerging party system, it asks: is this the New Normal? Michael Gallagher is Emeritus Professor of Comparative Politics at Trinity College Dublin, Ireland. Eoin O’Malley is Associate Professor of Politics at Dublin City University, Ireland. Theresa Reidy is Professor in Government at University College Cork, Ireland.